Injury Epidemiology and Prevention in Racket Sports: A Systematic Review - Brigita Destiara Tanja; Mokhammad R.Abadi (Mutiara Pendidikan dan Olahraga, 2026)
This study examines the evolving landscape of racket sports and its implications for injury patterns among diverse athlete populations. Over the past decade, traditional sports such as tennis and badminton have remained popular, while emerging sports like padel, pickleball, and beach tennis have experienced rapid growth, attracting participants across a wide age spectrum. However, the high-speed, repetitive, and multidirectional demands of these sports increase the risk of musculoskeletal injuries, making it essential to understand their epidemiology for effective prevention. This systematic literature review followed PRISMA 2020 guidelines, analyzing peer-reviewed studies published between January 2020 and early 2025 from databases including PubMed, ScienceDirect, Europe PMC, and Open Alex. A total of 22 studies met the inclusion criteria, comprising randomized controlled trials, cohort studies, and cross-sectional surveys. Methodological quality was assessed using the Cochrane Risk of Bias Tool (RoB 2) and the Newcastle-Ottawa Scale (NOS). The findings reveal significant variation in injury prevalence across sports, ranging from 34.2% in recreational pickleball to 92% in competitive padel. Badminton injuries were predominantly acute and affected the lower limbs, while tennis showed a higher incidence of overuse injuries in the upper limbs and trunk. Padel players frequently experienced elbow overuse injuries, with higher rates reported among females. In contrast, pickleball injuries were largely associated with falls among older adults. Preventive interventions involving supervised, sport-specific functional training and structured warm-up programs were found to be most effective. In conclusion, injury burden in racket sports is substantial and influenced by both intrinsic and extrinsic factors, highlighting the need for targeted, sport-specific prevention strategies.